Effects of synbiotic-based Bifidobacterium animalis in female rats experimentally infected with Toxoplasma gondii - Ribeiro, Claudia Mello [UNESP]; Costa, Veruska Maia [UNESP]; Franchi Vasconcelos Gomes, Maria Isabel [UNESP]; Golim, Marjorie de Assis [UNESP]; Modolo, José Rafael [UNESP]; Langoni, Hélio [UNESP] (Elsevier B.V., 2011)
The aim of this study was to assess the effects of a synbiotic composed of Bifidobacterium animalis and fructooligosaccharides on female rats infected with Toxoplasma gondii. Female Wistar rats, treated or not with dexamethasone, were daily supplemented with synbiotics for 21 days. After 15 days of supplementation, the rats were orally infected with 10(4) T. gondii bradyzoites. Blood samples were collected to measure the levels of IFN-gamma, IL-10 and T. gondii antibodies. All synbiotic-supplemented rats survived until the end of the experiment; however, non-supplemented dexamethasone-treated rats died between the fifth and the eighth days after T. gondii infection. Dexamethasone-treated rats supplemented with synbiotics (P < 0.05) were capable of synthesizing IFN-gamma, and this immunological response was essential to ensure their survival. In addition, brain cysts were found in one rat not supplemented with synbiotics. Results suggest that the synbiotic composed of B. animalis and fructooligosaccharides may be beneficial to toxoplasmosis control. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Synbiotics; Bifidobacterium animalis; Interferon-gamma; Interleukin-10; Toxoplasma gondii